Waist circumference as a marker for screening nonalcoholic fatty liver disease in obese adolescents - Ana Paula Grotti Clemente; Bárbara Dal Molin Netto; Joana Pereira de Carvalho-Ferreira; Raquel Munhoz da Silveira Campos; Aline de Piano Ganen; Lian Tock; Marco Túlio de Mello; Ana Raimunda Dâmaso (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: To assess the relationship between the degree of waist circumference (WC) and nonalcoholic fatty liver disease (NAFLD) in obese adolescents of both genders, analyzed according to quartiles of WC. Methods: Cross-sectional study that involved 247 obese adolescents aged 12-19 years. Mean values of the nutritional parameters and serum analyses were compared with the groups using the independent t-test. Pearson correlation coefficient was used to determine the relationship of the parameters studied. Chi-square test for trend was used to determine the relationship between the prevalence of the NAFLD and WC quartile by gender. Results: NAFLD were presented in 60% of the study participants. Obese adolescents in the 3rd and 4th quartiles of WC presented higher prevalence of NAFLD when compared with that in the 1st quartile in both genders. The NAFLD patients had significantly higher values for body weight, BMI (body mass index), BAZ-score (BMI-for-age z-scores), total fat (% and kg), WC, visceral fat, insulin, insulin resistance index (HOMA-IR), aspartate aminotransferase and alanine aminotransferase, when compared with non-NAFLD obese adolescents. Conclusions: In conclusion, the results presented here suggest that an increase in WC can reliably predict the risk of NAFLD in obese adolescents. This is a low cost and easy-to-use tool that can help in screening in adolescents.